2021
DOI: 10.1093/jb/mvab020
|View full text |Cite
|
Sign up to set email alerts
|

Components from spider venom activate macrophages against glioblastoma cells: new potential adjuvants for anticancer immunotherapy

Abstract: Immunomodulation has been considered an important approach in the treatment of malignant tumors. However, the modulation of innate immune cells remains an underexplored tool. Studies from our group demonstrated that the Phoneutria nigriventer spider venom (PnV) administration increased the infiltration of macrophage in glioblastoma, in addition to decreasing the tumor size in a preclinical model. The hypothesis that PnV would be modulating the innate immune system led us to the main objective of the present st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Glioblastoma resistance to bevacizumab occurs due to an immunosuppressive microenvironment triggered by VEGF ( Tamura et al, 2019 ). Thus, modulation of the immune response is the strategy of choice for malignant tumors such as glioblastoma ( Munhoz et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Glioblastoma resistance to bevacizumab occurs due to an immunosuppressive microenvironment triggered by VEGF ( Tamura et al, 2019 ). Thus, modulation of the immune response is the strategy of choice for malignant tumors such as glioblastoma ( Munhoz et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…LW9 induced a balance between pro- and anti-inflammatory cytokine release and an activated morphology of DCs. We recently demonstrated that the same molecule, LW9, induced an activated profile of macrophages [ 16 ]. It has been shown that PnV is composed mainly of small proteins, enzymes and peptides [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results lead us to investigate whether PnV components activate immune cells. A recent study demonstrated that, in fact, the venom induced a phagocytic and active macrophage profile [ 16 ]; however, there is no information so far concerning the effects of PnV on the adaptive immune system. In this sense, the present study aims to evaluate the effect of PnV and its purified components as adjuvants in the activation of DCs, focusing on the treatment of GB.…”
Section: Introductionmentioning
confidence: 99%
“…The above-mentioned PnV fractions were found to increase the number of monocytes in the blood of xenogeneic mice and the number of macrophages infiltrating in the tumor ( 130 ). It was demonstrated that the PnV spider venom fraction LW-9 increased cytotoxic and phagocytic activity of macrophages by immunomodulation ( 59 ). It was suggested that macrophages were reeducated into a non-TAMs phenotype, resulting in enhanced destruction of cancer cells.…”
Section: Molecular Background Of Action Of Venom Peptides On Glioblas...mentioning
confidence: 99%